2018
DOI: 10.1172/jci121960
|View full text |Cite
|
Sign up to set email alerts
|

Circulating and intrahepatic antiviral B cells are defective in hepatitis B

Abstract: B cells are increasingly recognized as playing an important role in the ongoing control of hepatitis B virus (HBV). The development of antibodies against the viral surface antigen (HBV surface antigen [HBsAgs]) constitutes the hallmark of resolution of acute infection and is a therapeutic goal for functional cure of chronic HBV (CHB). We characterized B cells directly ex vivo from the blood and liver of patients with CHB to investigate constraints on their antiviral potential. Unexpectedly, we found that HBsAg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
267
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(283 citation statements)
references
References 75 publications
14
267
2
Order By: Relevance
“…Besides, although B cells had a higher 4‐1BBL expression in patients with CHB, and the 4‐1BBL+ B cells also expressed high levels of costimulatory molecules and could activate T cells in vitro. In the present study, the overall activation of T cells in patients with CHB was not observed, reflecting the dysfunction of B and T cells in antiviral immunity during chronic HBV infection …”
Section: Discussioncontrasting
confidence: 50%
“…Besides, although B cells had a higher 4‐1BBL expression in patients with CHB, and the 4‐1BBL+ B cells also expressed high levels of costimulatory molecules and could activate T cells in vitro. In the present study, the overall activation of T cells in patients with CHB was not observed, reflecting the dysfunction of B and T cells in antiviral immunity during chronic HBV infection …”
Section: Discussioncontrasting
confidence: 50%
“…In mice, T-bet + B cells have been shown to be important for antiviral humoral immunity (34,62,63). In humans, T-bet + B cells have been detected in peripheral blood in a variety of chronic inflammatory contexts including systemic lupus erythematosus (64,65), chronic malaria exposure (66,67), and chronic viral infection (16,40,68). Although a universal definition and designated function for these cells remains elusive, T-bet + B cells are often classified as atypical memory B cells and, at least in some contexts, are thought to arise from repetitive BCR stimulation (17).…”
Section: Discussionmentioning
confidence: 99%
“…64 Interestingly, a recent study indicated that PD-1 was also overexpressed in hepatitis B surface antigen (HBsAg)-specific B cells. 65,66 These HBsAg-specific B cells had a marked reduction of antibody production that could be partially revived by PD-1 blockade. 65,66 These findings suggest that the suppressive role of ICs may extend beyond virus-specific T cells to virus-specific B cells.…”
Section: The Regulation Of Multiple Ics During Chronic Hbv and Hcv mentioning
confidence: 99%
“…65,66 These HBsAg-specific B cells had a marked reduction of antibody production that could be partially revived by PD-1 blockade. 65,66 These findings suggest that the suppressive role of ICs may extend beyond virus-specific T cells to virus-specific B cells. Beyond PD-1 Recent studies indicate a critical role of TIGIT in chronic viral infections.…”
Section: The Regulation Of Multiple Ics During Chronic Hbv and Hcv mentioning
confidence: 99%